2020
DOI: 10.1111/bjet.13047
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between educational television and mathematics capability in Tanzania

Abstract: Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low‐income countries when delivered in controlled settings. However, existing research in low‐resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A large body of research suggests that varying EdTech initiatives can positively impact learning outside of traditional school contexts, and we refer to a selection of the empirical evidence below 3 . Watson et al (2020) found child exposure to an educational television programme in Tanzanian out‐of‐school settings (eg, their home) to be significantly associated with mathematics capability. Radio interventions in at‐home settings can benefit mathematics learning (according to self‐reported data: Yelkpieri & Kweku, 2011—Ghana) and develop storytelling skills (Leguy & Mitsch, 2007—Mali).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of research suggests that varying EdTech initiatives can positively impact learning outside of traditional school contexts, and we refer to a selection of the empirical evidence below 3 . Watson et al (2020) found child exposure to an educational television programme in Tanzanian out‐of‐school settings (eg, their home) to be significantly associated with mathematics capability. Radio interventions in at‐home settings can benefit mathematics learning (according to self‐reported data: Yelkpieri & Kweku, 2011—Ghana) and develop storytelling skills (Leguy & Mitsch, 2007—Mali).…”
Section: Literature Reviewmentioning
confidence: 99%